BERPIKIR KRITIS SISWA DALAM PENYELESAIAN MATEMATIKA DITINJAU DARI PERBEDAAN TIPE GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Rahayu, Yuli Aulia; Winarso, Widodo (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
The essence of mathematics learning is the ability to solve math problems. Differences in ability, one of which is the suspect cognitive style. Based on the cause of the necessary mathematical problems of the students, cognitive style consists of a type of reflection and impulsive. So that the focus of this research is to analyze students' critical thinking skills in solving mathematical problems based on different types of reflective and impulsive cognitive style. Causal-comparative studies are needed to analyze the problem. The population of this study is composed of students of class VII SMPN 1 Susukan Cirebon. While the sample search uses the intentional sampling technique with the number of research samples 31 students. The technique of data collection using the Cognitive Style TMF test (correspondence familiar figures Test) and description Test (essay) Mathematics of critical thinking. The hypothesis test used is the t-test (T-test for independent samples). The results of the research show that the distribution of cognitive styles of students at SMPN 1 Susukan Cirebon, dominated by reflective-type cognitive style students (74% of students), while a small part of the students type of impulsive cognitive style (26% of students ). Critical thinking ability of reflective type students of cognitive style is better than the type of impulsive cognitive style students